Production and Characterization of Biogenic Manganese Oxides by Manganese-adaptedPseudomonas putidaNRRL B-14878 - Comert, Semih; Tepe, Ozlem (Taylor & Francis Inc, 2020)
Biogenic manganese oxides are believed to be the most abundant and highly reactive Mn oxide phases in the environment. In this study, the production of biogenic manganese oxides byPseudomonas putidaNRRL B-14878 was performed. First, a series of experiments were gradually carried out for the adaptation ofP. putidaNRRL B-14878 to Mn. Secondly, optimum pH and temperature for manganese oxidation by bacterium were determined as 7 and 28 degrees C, respectively.P. putidaNRRL B-14878 exhibited the highest Mn (II) oxidation performance (0.01025 mM/day) at pH of 7, 28 degrees C and Mn (II) concentration of 0.546 mM. Finally, characterization studies have revealed that biogenic manganese oxides are poorly crystallized and Mn (III) is the main valence state.
Keywords: Biogenic manganese oxides; characterization; Mn oxidation; Mn-oxidizing bacteria; Pseudomonas putida NRRL B-14878